THE LITERARY ENVIRONMENT OF JADIDIANITY AND KHOREZM (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the end of the 19th and beginning of the 20th centuries entered the history of the peoples of Central Asia as a “period of national revival.” The study of the problems of the socio-political and cultural-literary movement that took place during this period continues to this day. After all, the ideas of social development, human identity, independence of the Motherland are the social ideals of this movement and are eternal values that do not age. Modern research is increasingly revealing new manifestations of this complex, multifaceted process in education, artistic creativity, art, printing and other areas, humanitarian views of national and universal content.